Transformations - Claudius Gräbner-Radkowitsch; Jakob Kapeller; Stephan Pühringer (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2025)
Transformation is key term in the broader study of socio-economic provisioning system that has gained increased prominence and visibility in recent years due to intensifying economic, social and ecological risks and crises in the global economy. In this short review we assess key understandings of transformation in the recent literature and map how these understandings build on, extend and potentially deviate from classic accounts of socio-economic change as found classic accounts of evolutionary institutionalism.
Additional information: This paper will be published in a revised version in the Elgar Encyclopedia of Evolutionary and Institutional Economics, edited W. Elsner & W. Waller and published by Edward Elgar.
Keywords: 330; development; economic evolution; social change; transition; disruption